PENDAPATAN USAHA TERNAK KAMBING DI KELURAHAN TONDO KECAMATAN PALU TIMUR - Rahayu, Ritha (FAPETKAN UNTAD, 2014)
The research was conducted to determine the income level of the goat farmers in Tondo District of East Palu, particularly the former employees of PT. Iradat Puri. The location and respondents weredeterminedby purposive sampling. The analysis of income was applied in this study.The result showed that the average income of farmers from the business in a year was about Rp 7,964,375.- This research showed that the income of goat farmersstill remained low. The increasing of the goat farmer income from this business was very depended on the capital and the improvement of the farmer knowledge on technical maintenance as well as the business management. Keywords :Goat, Income, Farmer.